Some Theorems on Multiplicative Metric Spaces - Rani, Priyanka; V. Jagannadha Rao, G. V. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The aim of this paper is to discuss the fixed point theorems under some contractive conditions in multiplicative spaces. We also give their appropriate examples